Prevalence of Dental Caries in 5- and 6-Year-Old Myanmar Children. (28th April 2019) - Nomura, Yoshiaki; Maung, Khin; Kay Khine, Eint Min; Sint, Khin Myo; Lin, May Phyo; Win Myint, Min Khaing; Aung, Thu; Sogabe, Kaoru; Otsuka, Ryoko; Okada, Ayako; Kakuta, Erika; Wint, Wit Yee; et al.
Abstract : There are no national data available of the oral health in Myanmar. In this study, we examined dental caries status of 187 school children located in the suburban area of Naypyidaw, capital of Myanmar, at the age of five and six and analyzed by the individual level and tooth level. Maxillary D and B were sensitive for dental caries almost at the same level. They were less sensitive than maxillary A. Mandibular A and B were tolerant for dental caries. Prevalence of dental caries in Myanmar children was still high. By applying item response theory and multilevel modeling, tooth level analysis can be implemented to confirm the tendency for sensitivity or tolerance for dental caries by the tooth level.